Managing Difficulties in Supervision: Supervisors’ Perspectives. - Grant, Jan; Crawford, S.; Schofield, M. (American Psychological Association, 2012)
Few studies have examined the practice wisdom of expert supervisors. This study addresses this gap by exploring how experienced supervisors manage difficulties in supervision in the context of the supervisory relationship. The supervisors were a purposive sample of 16 senior members of the profession with considerable expertise in supervision. In-depth interviews were first conducted with the supervisors. An interpersonal process recall method was then used to explore their reflections on one of their DVD-recorded supervision sessions. Analysis of transcripts was completed using a modified consensual qualitative research method. Major difficulties included the broad domains of supervisee competence and ethical behavior, supervisee characteristics, supervisor countertransference, and problems in the supervisory relationship. Supervisors managed these difficulties using 4 key approaches: relational (naming, validating, attuning, supporting, anticipating, exploring parallel process, acknowledging mistakes, and modeling); reflective (facilitating reflectivity, remaining mindful and monitoring, remaining patient and transparent, processing countertransference, seeking supervision, and case conceptualizing); confrontative (confronting tentatively, confronting directly, refusing/terminating supervision, taking formal action, referring to personal therapy, and becoming directive); and avoidant interventions (struggling on, withholding, and withdrawing).Two brief case studies illustrate the process of applying these strategies sequentially in managing difficulties. The study highlights the importance of relational strategies to maintain an effective supervisory alliance, reflective strategies—particularly when difficulties pertain to clinical material and the supervisory relationship—and confrontative strategies with unhelpful supervisee characteristics and behaviors that impede supervision.